I have 5 questions:
1. Add the two expressions.
8k + 4 and 3k + 8
2.Add the two expressions.
6q + 1 and q + 11
3.Add the two expressions.
−4.2x+3 and 2.5x−6
4.Subtract h + 3 ​​from​ 6h + 1.
5.Subtract −b+3 ​​from −11b−4 ​.
PLEASE ANSWER AS SOON AS POSSIBLE EVEN IF YOU ONLY KNOW SOME OF THE PROBLEMS!

Respuesta :

8k+4 + 3k+8 = 11k+12
6q+1 + q+11 = 7q+12
-4.2x+3 + 2.5x-6= -1.7x-3
6h+1 -( h+3) = 5h-2
-11b-4 - (-b+3) = -10b-7
QUESTION 1


We want to add the following expressions:

[tex]8k + 4 [/tex]
and

[tex]3k + 8[/tex]



We set up the addition as follows:


[tex](8k + 4 ) + (3k + 8)[/tex]



We regroup the terms to obtain;


[tex] = 8k + 3k + 4 + 8[/tex]


We simplify to obtain,

[tex] = 11k + 12[/tex]


QUESTION 2


We want to add

[tex]6q + 1[/tex]
and

[tex]q + 11[/tex]


We add to obtain,


[tex](6q + 1) + (q + 11)[/tex]


We re group the terms to get,

[tex] = 6q + q + 11 + 1[/tex]


We simplify to obtain,

[tex] = 7q + 12[/tex]


QUESTION 3

The given expressions are

[tex] - 4.2x + 3[/tex]

and

[tex]2.5x - 6[/tex]


We add to obtain,



[tex] (- 4.2x + 3) + (2.5x - 6)[/tex]


We regroup like terms to obtain,


[tex] = - 4.2x + 2.5x - 6 + 3[/tex]



We simplify to get;


[tex] - 1.7x - 3[/tex]


QUESTION 4

We want to subtract

[tex] h+ 3[/tex]

from

[tex]6h + 1[/tex]


We subtract to obtain;

[tex] = (6h + 1) - (h + 3)[/tex]


We expand the bracket using the distributive property to obtain,


[tex] = 6h + 1 - h - 3[/tex]


We regroup the like terms to obtain,


[tex] = 6h - h + 1 - 3[/tex]

[tex] = 5h -2[/tex]




QUESTION 5

We want to subtract


[tex] -b + 3[/tex]

from

[tex] - 11b - 4[/tex]


We subtract to obtain

[tex]( - 11 b- 4) - ( - b + 3)[/tex]


We expand the brackets to get,

[tex] = - 11 b- 4+ b - 3[/tex]


We regroup the like terns to get,


[tex] = - 11 b+ b - 3 - 4[/tex]


This simplifies to;


[tex] = - 10 b - 7[/tex]